Protein kinase Cα stimulates hypoxia-induced pulmonary artery smooth muscle cell proliferation in rats through activating the extracellular signal-regulated kinase 1/2 pathway - Jiang, Rui (Mol Med Rep, 2017)
Hypoxic pulmonary hypertension (HPH) may contribute to vascular remodeling, and pulmonary artery smooth muscle cell (PASMC) proliferation has an important role in this process. However, no relevant information concerning the role and mechanism of protein kinase C (PKC)α in hypoxia-induced rat PASMC proliferation has been elucidated. The present study aimed to further investigate this by comparison of rat PASMC proliferation among normoxia for 72 h (21% O(2)), hypoxia for 72 h (3% O(2)), hypoxia + promoter 12-myristate 13-acetate control, hypoxia + safingol control, hypoxia + PD98059 control and hypoxia + U0126 control groups. The present study demonstrated that protein expression levels of PKCα in rat PASMCs were elevated. In conclusion, through activating the extracellular signal-regulated 1/2 signaling pathway, PKCα is involved in and initiates PASMC proliferation, thus bringing about pulmonary artery hypertension. These results add to the understanding of the mechanism PKCα in PH formation and lays a theoretical basis for prevention as well as treatment of HPH.